PENINGKATAN PRESTASI BELAJAR BAHASA INDONESIA PADA MATERI PUISI MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE DI KELAS II SD NEGERI 08 SUNGAI RAYA - DWI KARINA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research aims to improve Indonesian language learning achievement in poetry material through the picture and picture learning model in class II at SDN 08 Sungai Raya. This research uses classroom action research methods. This research uses a qualitative approach. The research subjects were Class II students at SD Negeri 08 Sungai Raya for the 2019/2020 academic year, totaling 17 students and consisting of 14 male students and 3 female students. Data collection techniques use observation, interviews and test results. Data analysis uses data reduction, data presentation, and drawing conclusions. The application of the Picture and Picture Learning Model can increase students' learning activities in the Indonesian language subject Poetry material for Class II students in the second semester of SD Negeri 08 Sungai Raya for the 2019/2020 academic year which can be seen from the increase in learning activities from cycle I to cycle II , from the Moderately Active category with an average value of 3.2 to the Active category with an average value of 4.1. Student learning achievement in the Indonesian language subject Class II semester II at SD Negeri 08 Sungai Raya for the 2019/2020 academic year has increased in each cycle with the percentage of classical completion in each cycle, namely cycle I at 70% and cycle II at 100%. % means there is an increase of 30%. ABSTRAKPenelitian ini bertujuan untuk meningkatkan prestasi belajar bahasa Indonesia pada materi puisi melalui model pembelajaran picture and picture di kelas II SDN 08 Sungai Raya. Penelitian ini menggunakan metode penelitian tindakan kelas. Penelitian ini menggunakan pendekatan kualitatif. Subyek penelitian adalah siswa Kelas II SD Negeri 08 Sungai Raya Tahun Pelajaran Tahun Pelajaran 2019/2020 yang berjumlah 17 siswa dan terdiri atas 14 siswa laki-laki dan 3 siswa perempuan. Teknik pengumpulan data menggunakan observasi, wawancara, dan hasil tes. Analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan. Penerapan Model Pembelajaran Picture and Picture dapat meningkatkan aktivitas belajar para siswa pada mata pelajaran Bahasa Indonesia Materi Puisi siswa Kelas II semester II SD Negeri 08 Sungai Raya Tahun Pelajaran Tahun Pelajaran 2019/2020 yang dapat dilihat dari peningkatan aktivitas belajar dari siklus I sampai dengan siklus II, dari kategori Cukup Aktif dengan nilai rata-rata 3,2 sampai dengan kategori Aktif dengan nilai rata-rata 4,1. Prestasi belajar siswa pada mata pelajaran Bahasa Indonesia Kelas II semester II di SD Negeri 08 Sungai Raya Tahun Pelajaran Tahun Pelajaran 2019/2020 mengalami peningkatan pada setiap siklus dengan persentase ketuntasan secara klasikal masing-masing siklus yaitu siklus I sebesar 70 % dan siklus II sebesar 100 % berarti ada kenaikan 30 %.